The Transmission Mechanism of Monetary Policy - Mahadeva, Lavan; Sinclair, Peter (England: Centre for Banking Studies, 2001)
The transmission mechanism describes how monetary policy affects inflation and output.
osc 9/8/17
Loans
Keywords: Monetary Policy